Color Selection and Reproduction in Dentistry. Part 1: Fundamentals of Color - Schmeling DDS, MS, PhD, Max (Odovtos - International Journal of Dental Sciences, 2016)
Knowing the optical phenomena that determine the chromatic expression of tooth tissues and their clinical application are essential factors for obtaining esthetic excellence in restorative treatments. Tooth color matching with restorative materials is influenced by several factors, which can produce frustrating results, for both the professional and the patient, when they are not controlled. Based on scientific evidence, a sequence of three articles were performed describing the fundamentals of color formation, the characteristics of the light interaction with the dental tissues and restorative materials and the main methods of color selection and reproduction in esthetic dentistry.